PENGARUH PENGAWASAN INTERNAL TERHADAP KINERJA KARYAWAN PADA CV. BALI BINTANG TERANG DENPASAR - Putri Anggreni (Forum Manajemen STIMI Handayani Denpasar, 2019)
On this research will be analyzed about internal control influence to employee’s performance. Result obtained from this study is, there is positive and significant relationship between internal control to employee’s performance. This can be seen from correlation coefficient obtained is 0,940 so it can be said that internal control has very strong correlation to employee’s performance at CV. Bali Bintang Terang Denpasar. Hypothesis applied is accepted defines there is positive and significant impact between internal control to employee’s performance at CV. Bali Bintang Terang Denpasar. Determination analysis is obtained by determination coefficient as 88,3% means employee’s performance is influenced by internal control as 88,3% and remain 11,7% is influenced other factor not being studied.